Household choices, circumstances and equity of access to basic health and education services in the Philippines - Joseph J. Capuno; Aleli D. Kraft (University of the Philippines, School of Economics (UPSE), 2010)
In developing countries like the Philippines, a major policy concern is the inequity in access to health and education services. In this paper, we investigate the effects of factors over which households have control ('choices') or none ('circumstances') on their access to basic services. Our logit regression analyses of two nationwide household surveys reveal that household income and composition, mother's age and education status, and the child's age and gender are critical. The circumstance factors
Keywords: I18; I28; I38; 330; Philhealth coverage and some area-level characteristics of health and education services; Gesundheitsversorgung; Bildungschancen; Haushaltseinkommen; Konsumentenverhalten; Privater Haushalt; Philippinen